A retrospective quasi-experimental study of a community crisis house for patients with severe and persistent mental illness. (July 2013) - Siskind, Dan; Harris, Meredith; Kisely, Steve; Brogan, James; Pirkis, Jane; Crompton, David; Whiteford, Harvey
Objective: There is increasing international evidence that crisis houses can reduce the time spent in acute psychiatric inpatient units for patients with severe and persistent mental illness, at a lower cost and in an environment preferable to patients. We evaluated the Alternatives to Hospitalisation (AtH) program, a crisis house operating in outer suburban Brisbane. Methods: One hundred and ninety-three AtH patients were compared to 371 matched controls admitted to a peer hospital district acute psychiatric unit. Hospitalisations, demographics and illness acuity were compared one year before and after an acute index episode of residential care involving hospital and/or AtH. Hospital bed-days during the index episode were compared between AtH participants and controls. The cost of bed-days averted was compared to the cost of providing the AtH program. Results: AtH participants spent 5.35 fewer days in hospital during the index episode than controls, after adjustment for illness acuity, living conditions, marital status and emergency department (ED) presentations. Per patient cost of averted psychiatric inpatient bed-days, 5948.22, was higher than the per patient cost of providing AtH, 3071.44. AtH participants had higher levels of illness acuity, ED presentations and acute psychiatric admissions than controls in the year after the index episode. Conclusions: For acutely unwell, stably housed patients, able to be managed outside of a secure facility, a crisis house program can reduce acute psychiatric bed-days, providing a cost saving for mental health services.